2013
DOI: 10.1152/ajpendo.00171.2012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and immunomodulatory effects of n-3 fatty acids are different in mesenteric and epididymal adipose tissue of diet-induced obese mice

Abstract: Ludwig T, Worsch S, Heikenwalder M, Daniel H, Hauner H, Bader BL. Metabolic and immunomodulatory effects of n-3 fatty acids are different in mesenteric and epididymal adipose tissue of diet-induced obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 85 publications
(110 reference statements)
4
39
2
1
Order By: Relevance
“…50 In our study, neither dietary TMAO nor fish oil had any significant influence on the mRNA expression of macrophage markers F4/80 and CD11b. 50 In our study, neither dietary TMAO nor fish oil had any significant influence on the mRNA expression of macrophage markers F4/80 and CD11b.…”
Section: Discussioncontrasting
confidence: 68%
“…50 In our study, neither dietary TMAO nor fish oil had any significant influence on the mRNA expression of macrophage markers F4/80 and CD11b. 50 In our study, neither dietary TMAO nor fish oil had any significant influence on the mRNA expression of macrophage markers F4/80 and CD11b.…”
Section: Discussioncontrasting
confidence: 68%
“…Both murine and human studies have shown that MAT mass and function is altered in mice and humans suffering from colitis, indicating an active interaction between the intestine and MAT [35e37]. Furthermore, diet has a more pronounced influence on MAT compared to other, more distant, ATdepots [38,39]. Therefore, it can be hypothesized that MATinflammation has a direct influence on the intestine, possibly influencing the enteric endocrine system.…”
Section: Discussionmentioning
confidence: 99%
“…This led to an emerging interest in the role of mitochondria in NAFLD and nonalcoholic steatohepatitis (Guo et al, 2013;Thomas et al, 2013;Li et al, 2014;Nesteruk et al, 2014). Most of these studies investigated the development of fatty liver in mice at juvenile life stages and clearly demonstrate that fat accumulation in adolescent mice can be induced by high fat diet depending on the fat source and the duration of feeding (Satapati et al, 2012;Fontana et al, 2013;Ludwig et al, 2013;Nakamura and Terauchi, 2013). In humans, the prevalence of metabolic diseases, including NAFLD, increases with age (Sheedfar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In our effort to trace the early molecular events that facilitate the development of an imbalance in hepatic fatty acid metabolism, we aimed to delineate age-and dietrelated effects at an early stage of disease development. A previous study demonstrated that 12 weeks of feeding our control and high fat diet are sufficient to increase hepatic triglyceride content in adolescent mice (Ludwig et al, 2013). To study the effect of age on this process at an even earlier stage, we applied a fixed period of 9 weeks high fat feeding in adolescent (A), young adult (YA), and middleaged (MA) mice.…”
Section: Introductionmentioning
confidence: 99%